Uso de polímeros funcionais em dispositivos para energy harvesting - Mendes, Bruno de Oliveira (Universidade Federal de São Carlos, 2024)
The world is looking for ways to obtain energy more efficiently since society has become highly dependent on electricity for the most diverse daily activities. The traditional means of obtaining it are those that generate enough energy for humanity, however, several daily movements have a high potential and end up not being explored. This range of dissipated energy is precisely the repressed demand on which energy capture devices seek to act and were developed, creating the concept of Energy Harvesting, which began to be studied in the 21st century with the development of nanogenerators. The devices use principles that make it possible to generate electrical energy such as piezoelectricity and triboelectricity. Therefore, the choice of materials to be used is extremely important and to expand the range of application, polymers are good candidates for the development of these parts due to their properties. The use of nanogenerators to capture energy depends on the characteristics of each material used in the device and the way in which it is manufactured. One can explore energies present in the human body and in nature, therefore, for each use, it is necessary to analyse the best shape, material and way of functioning of each device. Studies are developed in the most diverse applications and with different material possibilities, however, piezoelectricity in polymers is mostly PVDF, a material that has the ability to generate electrical energy from external loads, while triboelectricity is easily explored since it only depends on two different materials and the friction between them is already capable of separating charges, generating a current. Therefore, the potential for exploring nanogenerator devices based on triboelectricity is great and enables the development of new ways to obtain energy and to be used across the globe to change global energy consumption in search of more sustainable and that generate less impact in all spheres.
Use of functional polymers in energy harvesting devices
Keywords: Captura de energia; Polímeros; Piezoeletricidade; Triboeletricidade; Energy harvesting; Polymers; Piezoelectricity; Triboelectricity; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS